STUDY OF D-DIMER AND SERUM FERRITIN LEVELS AS PROGNOSTIC BIOMARKERS IN COVID-19 PATIENTS - SOGANI, SONAL; PRAJAPAT, RAJNEESH; TOMAR, JYOTI; JAIN, SUMAN; BAPNA, ANJU (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Objective: Coronavirus disease 2019 (COVID-19) is primarily a respiratory illness causing thrombotic disorders. Pro-inflammatory cytokines are one of the responsible causes of cytokine storm syndrome in patients with COVID-19. Coagulopathy and inflammation are associated with COVID-19 severity. The coronavirus spike protein facilitates the entry of the virus into the target cells causing coagulopathy and inflammation.Other infections include direct viral toxicity, endothelial cell damage, inflammation, and deregulation of the immune response and renin-angiotensin-aldosterone system. The study aims to estimate levels of D-Dimer and Serum Ferritin in symptomatic and asymptomatic COVID-19 patients and its comparison with healthy controls. Methods: The study includes 30 healthy control and 30 symptomatic and 30 asymptomatic COVID-19 patients of both sexes. Analysis of serum ferritin was done on a fully automated immunology analyzer-SIEMENS based on the principle of chemiluminescence. D-dimer was estimated on mLab which is cartridge-based. Results: We observed that the levels of D-Dimer and Serum Ferritin significantly increased in symptomatic COVID-19 patients as compared to asymptomatic COVID-19 positive patients and healthy non-COVID-19 controls. Conclusion: The elevated serum ferritin and D-dimer were associated with a poor outcome and poor prognosis and could predict the worsening of COVID-19 patients. The significant increase showed that D-Dimer and serum ferritin accurately predicts patients developing severe COVID- infection.